Algorithm for generation pseudo-random series with arbitrarily assigned distribution law - Єременко, В.С.; Мокійчук, В.М.; Самойліченко, О.В. (Proceedings of National Aviation University, 2005)
Method for generation pseudo-random series with arbitrarily assigned distribution law has been proposed. The praxis of using proposed method for generation pseudo-random series with anti-modal and approximate to Gaussian distribution law has been investigated.